Management of Psychosis in a Patient with Probable Dopa-Responsive Dystonia - Wang, Maggie; Sison, Joseph I. (Case Reports in Psychiatry, 2018)
Dopa-responsive dystonia is a rare childhood neurological disorder characterized by asymmetric dystonia, predominantly of the lower limb, that responds excellently to levodopa replacement therapy. Although it is known that behavioral changes, such as depression, anxiety disorders, and sleep disturbances, typically follow onset of motor symptoms, there is limited literature on the psychiatric symptoms of this disorder. This report describes a novel case of a 20-year-old male with a history of dopa-responsive dystonia and schizoaffective disorder who presented with both dystonia and psychosis after a period of medication noncompliance. This case provides a reference for the management of psychosis in patients with dopa-responsive dystonia and highlights the need for more research on the nonmotor symptoms that accompany this neurological disorder.